Exploring energy transfer between pyrene complexes and europium ions - potential routes to oxygen sensors - Hueting, R; Tropiano, M; Faulkner, S (Royal Society of Chemistry, 2014)
Pyrene chromophores are shown to exhibit reversible energy transfer to europium ions, resulting in oxygen dependent lanthanide luminescence. Two different pathways can give rise to oxygen dependence: rapid reversible energy transfer between the T1 state and the emissive state, or slow T1-5D0 energy transfer on the timescale of triplet state quenching. This journal is